2003
DOI: 10.1053/jvet.2003.50024
|View full text |Cite
|
Sign up to set email alerts
|

Elution of Metronidazole and Gentamicin from Polymethylmethacrylate Beads

Abstract: (ABSTRACT)Ten polymethylmethacrylate (PMMA) beads containing metronidazole (3 concentrations); gentamicin sulfate; or metronidazole and gentamicin sulfate were immersed in 5 ml of phosphate buffered saline in triplicate. Eluent was replaced at specified time intervals for 1 day (1, 3, 6, 12 and 24 hours), daily, or weekly for 21 days.Antibiotic concentrations were measured by High Performance Liquid Chromatography.Changes in antibiotic bioactivity attributable to polymerization or co-polymerization of the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 47 publications
(244 reference statements)
0
30
0
Order By: Relevance
“…55,56,57 Ramos et al reported that neither polymerization, gas sterilization, nor 2 month storage of AIPMMA with varied antibiotics affected the bioactivity of the antibiotic against a common pathogen. 10 In our study the MRT did differ significantly, suggesting that ethylene oxide sterilization resulted in slightly longer elution time, though there would likely be no clinical significance in this increase (7 hours).…”
Section: Chapter IV Statistical Analysismentioning
confidence: 46%
See 2 more Smart Citations
“…55,56,57 Ramos et al reported that neither polymerization, gas sterilization, nor 2 month storage of AIPMMA with varied antibiotics affected the bioactivity of the antibiotic against a common pathogen. 10 In our study the MRT did differ significantly, suggesting that ethylene oxide sterilization resulted in slightly longer elution time, though there would likely be no clinical significance in this increase (7 hours).…”
Section: Chapter IV Statistical Analysismentioning
confidence: 46%
“…Meropenem's elution pattern is biphasic, which is similar to patterns reported for other antibiotics. 10 This biphasic elution is suspected to be the result of initial antibiotic elution from the surface of the bead and a sustained release during the second phase of elution from the bead matrix. 54 Approximately 40% of the cumulative antibiotic elution occurred during the first hour.…”
Section: Chapter IV Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Nitroimidazole polymer complexes as hydrogels, beads used as colon targeted drug delivery systems is emerging [1,3,6,11,13,14,15,17,22]. Different polymers such as polyethylene glycol [9,20], poly vinyl alcohol [4,24], polymethylmethacrylate [16],polysaccharides [6,11]. Other uses of nitroimidazole polymer complexes as delivery systems are reported in periodontal diseases [2,21], amebiasis [6,13,22], helicobector pylori [7], gentamycin [16], vaginitis [8], gastritis [10,12], sprays [19], liposomes [25].…”
Section: Discussionmentioning
confidence: 99%
“…Of mention, gentamycin, helicobector pylori and amoeba microbes have been found as potential candidates as targeted nitroimidazole delivery [7,16,22]. Other options of liposomes as nitroimidazole delivery systems have been reported as minicapsular extrusion system [25].…”
Section: Discussionmentioning
confidence: 99%